Next-Generation Sequencing Analysis of the Human TCRγδ+ T-Cell Repertoire Reveals Shifts in Vγ- and Vδ-Usage in Memory Populations upon Aging - Kallemeijn, Martine J.; Kavelaars, François G.; van der Klift, Michèle Y.; Wolvers-Tettero, Ingrid L. M.; Valk, Peter J. M.; van Dongen, Jacques J. M.; Langerak, Anton W. (Frontiers in Immunology, 2018)
Immunological aging remodels the immune system at several levels. This has been documented in particular for the T-cell receptor (TCR)αβ+ T-cell compartment, showing reduced naive T-cell outputs and an accumulation of terminally differentiated clonally expanding effector T-cells, leading to increased proneness to autoimmunity and cancer development at older age. Even though TCRαβ+ and TCRγδ+ T-cells follow similar paths of development involving V(D)J-recombination of TCR genes in the thymus, TCRγδ+ T-cells tend to be more subjected to peripheral rather than central selection. However, the impact of aging in shaping of the peripheral TRG / TRD repertoire remains largely elusive. NGS analysis methods were optimized based on a spike-in method using plasmid vector DNA-samples for accurate TRG / TRD receptor diversity quantification, resulting in optimally defined primer concentrations, annealing temperatures and cycle numbers. Next, TRG / TRD repertoire diversity was evaluated during TCRγδ+ T-cell ontogeny, showing a broad, diverse repertoire in thymic and cord blood samples with Gaussian CDR3-length distributions, in contrast to the more skewed repertoire in mature circulating TCRγδ+ T-cells in adult peripheral blood. During aging the naive repertoire maintained its diversity with Gaussian CDR3-length distributions, while in the central and effector memory populations a clear shift from young (Vγ9/Vδ2 dominance) to elderly (Vγ2/Vδ1 dominance) was observed. Together with less clear Gaussian CDR3-length distributions, this would be highly suggestive of differentially heavily selected repertoires. Despite the apparent age-related shift from Vγ9/Vδ2 to Vγ2/Vδ1 no clear aging effect was observed on the Vδ2 invariant T nucleotide and canonical Vγ9-Jγ1.2 selection determinants. A more detailed look into the healthy TRG / TRD repertoire revealed known CMV-specific TRG / TRD clonotypes in a few donors, albeit without a significant aging-effect, while M. tuberculosis-specific clonotypes were absent. Notably, in effector subsets of elderly individuals we could identify reported TRG and TRD receptor chains from TCRγδ+ T-cell large granular lymphocyte (LGL) leukemia proliferations, which typically present in the elderly population. Collectively, our results point to relatively subtle age-related changes in the human TRG / TRD repertoire, with a clear shift in Vγ / Vδ usage in memory cells upon aging.